Pullout Strength of Screws in Foal Third Metacarpal Bone after Overdrilling a 4.5 mm Hole - Sedrish, S. A.; Moore, R. M.; Kelly, K.; Martin, G. S.; Burba, D. J. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
The purpose of the study was to determine and to compare the in vitro pullout strength of 5.5 mm cortical versus 6.5 mm cancellous bone screws inserted in the diaphysis and metaphysis of foal third metacarpal (MCIII) bones in threaded 4.5 mm cortical bone screw insertion holes that were then overdrilled with a 4.5 mm drill bit. This information is relevant to the selection of a replacement screw if a 4.5 mm cortical screw is stripped during orthopaedic surgery.In vitro pullout tests were performed in two independent cadaver studies, each consisting of 12 foal MCIII bones. Two 4.5 mm cortical screws were placed either in the mid-diaphysis (study 1) or distal metaphysis (study 2) of MCIII bones. The holes were then overdrilled with a 4.5 mm bit and had either a 5.5 mm cortical or a 6.5 mm cancellous screw inserted; screw pullout tests were performed at a rate of 0.04 mm/s until screw or bone failure occurred.The bone failed in all of the tests in the diaphyseal and metaphyseal bone. The holding power for 6.5 mm cancellous screws was significantly (p <0.05) greater than for 5.5 mm cortical screws in both the diaphysis and metaphysis. There was not any difference in the holding power of screws in either the diaphysis or the metaphysis between proximal and distal screw holes.If a 4.5 mm cortical bone screw strips in MCIII diaphyseal or metaphyseal bone of foals, a 6.5 mm cancellous screw would provide greater holding power than a 5.5 mm cortical screw.In order to provide information regarding selection of a replacement screw if a 4.5 mm cortical screw is stripped, the in vitro pullout strength was determined for 5.5 mm cortical and 6.5 mm cancellous screws inserted in third metacarpal diaphyseal and metaphyseal bone of foals in which threaded 4.5 mm cortical bone screw insertion holes had been overdrilled with a 4.5 mm bit. The holding power of the 6.5 mm cancellous screw was significantly greater than the 5.5 mm cortical screw in both the diaphysis and metaphysis of foal third metacarpal bone. Thus, it appears that if a 4.5 mm cortical screw is stripped during orthopaedic surgery in foals, a 6.5 mm cancellous screw would provide superior holding power.
Keywords: In vitro; pullout strength; orthopaedic screws; foal; third metacarpus